Development of a Tool for the Assessment of Job Satisfaction amongst the Community Health Workers - G Revadi; Jalindar Baravakar; Amit Kumar; Ankur Joshi; Abhijit P. Pakhare (Preventive Medicine: Research & Reviews)
Introduction: Amongst the various factors influencing the performance of community health workers (CHWs), job satisfaction serves as a potential drive to perform better. This study aimed at developing a tool to measure how well the CHWs are satisfied pertaining to individual, community and health system determinants. Methodology: This cross-sectional study was conducted in a rural block of Madhya Pradesh (Central India). The CHWs were administered a self-reported questionnaire that contained individual, health system and community level determinants of job satisfaction with a 5-point Likert scale to mark their perception. Results: The job satisfaction scale of 15 items was initially administered to the 92 CHWs. Their scale content validity index (average) was 0.83. The finalised tool consisted of 13 items under three factors following the exploratory factor analysis namely, health system, supervision and peer support and intrinsic job satisfaction. Their overall Cronbach’s alpha was 0.81, with the median (interquartile range) score of job satisfaction for both the Relatively Low Performing and Relatively High Performing Community Health Workers being 4 (4–5). Conclusion: The CHWs in this study were satisfied with their performance as voluntary village health workers following the assessment using a complex job satisfaction scale.